Evaluating Scientific Research Outputs: A Comprehensive Guide to Bibliometric Methodology - Swati Gupta; Praveen Babel (Exploration of Knowledge and Information in Sciences, Edition 1, 2025)
The present study highlights the bibliometric methods, which aid in evaluating the scientific work of scholars and faculty members etc. Scientists can also use this strategy to look into the strategic and historical expansion of publishing books across a variety of domains. It may also help investigators from other nations considering the literature is available in a variety of languages and may be accessed from many longitudes. Statistical approaches have been gaining prominence as a means for evaluating scientific study outcomes. Numerous bibliometric factors were utilized to analyze the publications, such as article contributions over time, authorship patterns, gender-based contributions, highly cited authors, titles, document type, and furthermore. It emerged as extremely advantageous to produce accurate statistical data using numerous analytic methods, tools, and software, such as Sci2, Sitkis, and VOSviewer. This paper also explores whether its approaches are enhanced by its laws, elements, measurements, indicators, applications, and other features.